2014
DOI: 10.11607/jomi.3446
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiographic Evaluation of Early Loaded Maxillary Anterior Single-Tooth Bone-Level Implants

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 0 publications
0
21
0
3
Order By: Relevance
“…There are different treatment options in dentistry for the rehabilitation of anterior tooth loss including implant‐supported prosthesis (ISP), traditionally fixed bridge prosthesis (FBP), and resin‐bonded fixed dental prosthesis (RBFDP). In recent years, ISP has gained importance when replacing missing single teeth adjacent to caries free teeth . However, it is not possible to place the implant directly to the edentulous area in every patient.…”
Section: Introductionmentioning
confidence: 99%
“…There are different treatment options in dentistry for the rehabilitation of anterior tooth loss including implant‐supported prosthesis (ISP), traditionally fixed bridge prosthesis (FBP), and resin‐bonded fixed dental prosthesis (RBFDP). In recent years, ISP has gained importance when replacing missing single teeth adjacent to caries free teeth . However, it is not possible to place the implant directly to the edentulous area in every patient.…”
Section: Introductionmentioning
confidence: 99%
“…Patient sex, age, and number: Among the included studies, 10 did not mention patient sex 1,10,22,23,[26][27][28][29][30][31] . Between all the studies mentioning mean age, maximum mean ages in Tables 1-3 were 65.8 1 , 54.63 32 , and 60 30 , respectively, while minimum amounts were 33 24 , 36 28 , and 39 33 in order.…”
Section: Resultsmentioning
confidence: 86%
“…However, dynamic loading increases the potential for such bacterial penetration 17,21 . Platform-switching has been introduced as a method to shift the stress inward and enhance hard tissue stability, papilla maintenance, and the soft tissue seal 16,19,[22][23][24][25] . A study reported 0.7 mm versus 2.5 mm bone loss compared to the conventional connection design after 6 months of loading while the other design exhibited 0.12 mm versus 0.29 mm bone loss after one year 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Os estudos com pilares de zircônia mostram 100% de taxa de sucesso em acompanhamentos clínicos de 1 a 5 anos para próteses unitárias localizadas tanto na região anterior como posterior, e para PPFs [10,11,[17][18][19][20][21][22]25]. Apenas dois estudos observaram fratura do pilar de zircônia; em um estudo uma fratura ocorreu no momento da instalação e outra após 2 meses, o que pode indicar algum tipo de falha no processamento desses pilares [18].…”
Section: Discussionunclassified
“…Já em um estudo mais longo (11 anos), o modo de falha deu-se através do afrouxamento de parafuso [24]. Esse modo de falha também foi encontrado em dois outros estudos [10,19], mas não foi considerado como falha do pilar pelos autores porque é um tipo de falha reparável. Northdurft et al [20] de zircônia foi de 100% em estudos de até 11 anos.…”
Section: Discussionunclassified